Analisis Kualitatif Efektivitas Pemasaran Digital Produk Ramah Lingkungan: Studi Kasus pada UMKM Eco-print Yasmin Wiwid - Monica Septiani; Muhamad Rafli Subadri; Berlintina Permatasari (Yayasan Literasi Sains Indonesia, 2026)
The development of digital technology and increasing public awareness of environmental issues have encouraged. MSMEs to adopt digital marketing to market environmentally friendly products. However, many MSMEs still experience limitations in implementing digital marketing effectively and in a structured manner. This study aims to analyze the digital marketing strategy implemented by the MSME Eco-print Yasmin Wiwid, identify factors influencing the effectiveness of digital marketing of environmentally friendly products, and develop an effective and sustainable digital marketing model. This research uses a qaheualitative approach with a case study method. Data collection was conducted through observation, in-depth interviews with business owners, and documentation. Data analysis was conducted using descriptive qualitative methods, referring to the Digital Marketing Mix (9P) concept: product, price, place, promotion, people, process, physical evidence, partnerships, and personalization, which are related to the characteristics of environmentally friendly products. The results show that the use of social media, particularly Instagram, plays a significant role in increasing brand awareness, expanding market reach, and building consumer trust. The effectiveness of digital marketing is influenced by the competence of human resources, the quality and consistency of digital content, the uniqueness of environmentally friendly products, and active interaction with consumers. This research produces a digital marketing model that integrates digital marketing strategies and green marketing principles to improve the competitiveness and sustainability of environmentally friendly MSMEs.